Exploring the association of levers of control and social capital in Asnaf entrepreneurship program: case studies on LZS and MAIWP / Nor Hayati Samba Mohamed - Mohamed, Nor Hayati Samba (2020)
Zakat institutions had introduced entrepreneurship programs to help eradicate poverty among productive asnaf. Increased expectation towards zakat institutions has led Lembaga Zakat Selangor (LZS) and Majlis Agama Islam Wilayah Persekutuan (MAIWP) to be managed like a private corporation which includes implementation of formal management control system (MCS). Another contributing factor to the success of entrepreneurship program mentioned by few scholars is Social Capital (SC). Despite the importance of MCS and SC, no previous research has studied the role of both in the context of zakat institutions. Therefore, the focus of this research is to investigate the association between MCS using levers of control (LOC) framework and SC in zakat institutions. Four main objectives of this research are as follows. The objectives are to determine LOC practices, types of SC that exist, how SC is being developed and to explain the association between LOC and SC in asnaf entrepreneurship programs by LZS and MAIWP. Since asnaf entrepreneurship programs are closely related to Islamic teaching and values in its operation, Philosophy of Zakat (POZ) is deems important to the study of these zakat institutions besides LOC and SC. A conceptual model of Asnaf Entrepreneurship Management Control System and Social Capital (AEMCSSCM) has been developed incorporating all the three theories, LOC, SC and POZ. Using a case study approach of entrepreneurship programs in LZS and MAIWP, various evidences were collected but focusing heavily on semi-structured interviews. A total of twenty one face-to-face interviews were conducted among zakat officers, consultants, and asnaf from both institutions. Findings showed that four types of LOC namely belief, boundary, interactive and diagnostic controls exist in both zakat institutions. Belief has been found to be an important control that leads to development of some controls under boundary, interactive and diagnostic. In terms of association, interactive control is expected to be very significant in the development of SC. While three types of SC which are bonding, bridging and linking had been found to be developed through norms, networking, trust and reciprocity. Finding of the research showed bonding has been developed strongly compared to bridging and linking SC. As a conclusion, MCS using LOC framework is expected to have associated with the development of SC. This research provides novel contribution in several ways. First, the development of AEMCSSCM which is able to explain the association between MCS and SC. From practical perspective, the results of this study can help zakat institutions identify methods in improving MCS and eventually help in developing SC in their entrepreneurship programs. Thus the findings of this research provide significant contribution to asnaf entrepreneurship program and zakat institutions particularly and any organizations involved in helping the poor and needy generally. Other zakat institutions in Malaysia as well as other Muslim countries can develop their asnaf entrepreneurship program and consider the importance of MCS in developing SC to ensure the success of the program. In the end, success of the asnaf entrepreneurship program will lead to effective zakat distribution, transforming asnaf to be zakat payers and contributing to socio-economic sustainability.